Antioxidant and anti-inflammatory properties of Ilex guayusa tea preparations: a comparison to Camellia sinensis teas. Issue 12 (14th November 2017) - Pardau, Madelein D.; Pereira, Andreia S. P.; Apostolides, Zeno; Serem, June C.; Bester, Megan J.
Abstract : Ilex guayusa teas are a good source of dietary phenolic compounds with cellular antioxidant and anti-inflammatory properties comparable to green and black Camellia sinensis teas. Abstract : Ilex guayusa tea preparations are now commercially available as Runa tea. Little is known regarding the antioxidant and anti-inflammatory bioactivities of this tea. The I. guayusa teas had a total polyphenolic content between 54.39 and 67.23 mg GAE per g dry mass and peroxyl radical scavenging capacities between 1773.41 and 2019 μmol TE per g dry mass, nearly half of that for the Camellia sinensis teas. The I. guayusa teas afforded 60–80% protection from oxidative stress in the Caco-2 cellular antioxidant assay, comparable to the C. sinensis teas. The anti-inflammatory activity in lipopolysaccharide-stimulated RAW 264.7 cells of I. guayusa teas was similarly comparable to the C. sinensis teas with nitric oxide production reduced by 10–30%. Major compounds identified by mass spectrometry were the phenolic mono- and dicaffeoylquinic acid derivatives. I. guayusa teas are a good source of dietary phenolic compounds with cellular antioxidant and anti-inflammatory properties.